Parameters evaluation of Unified Power Quality Conditioner - Haidar, Ahmed M. A.; Benachaiba, C.; Faisal, A. F. Ibrahim; Kamarul Hawari, Ghazali (IEEE, 2011)
The term of “Power Quality” is used to describe the electromagnetic phenomenon in variations of voltage and current in the power system. Most power quality disturbances can come from the facility itself, such as large loads turning on simultaneously, improper wiring and grounding practices, the start-up of large motors and electronic equipments that can be both a source and victim of power quality phenomena or from externally generated, for example, lightning strokes on the power lines. Currently, there are so many industries using a high technology for the manufacturing and requiring a high quality of power supply. Therefore, the paper is focusing mainly on power quality disturbance and the technique used to improve the quality of delivered power such as Unified Power Quality Conditioner (UPQC). A comprehensive analysis was performed on the parameters that affecting the performance UPQC and the MATLAB software has been used to simulate the test system. Based on the results of analysis, it can be confirmed that UPQC is an effective technique for quick improvement of power quality.